Analisis Foot Spa Diabetic terhadap Sirkulasi Darah Perifer Kaki Pasien DM Tipe 1 dan 2 - Nur Anisah; Ricky Riyanto Iksan; Meria Woro Listyorini; Wiwie Herdalisa; Ratih Bayuningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of diabetic foot spa on foot peripheral blood circulation in patients with type 1 and 2 DM. The method used was a pre-experimental study with a one-group pre-post test design. The population in this study were 32 respondents. Sampling technique with purposive sampling technique. The results showed that the statistical test paired t-test obtained a p value = 0.001 which means that diabetic foot spa is effective in improving the peripheral blood circulation of the feet in patients with type 1 and 2 DM. Health Center. Conclusion Diabetic foot spa is effective in improving the peripheral blood circulation of the feet. in type 1 and 2 DM patients. Keywords: Blood Circulation, Diabetes Mellitus, Diabetic Foot Spa,